Проєкційно-алгебраїчна апроксимація лінійних та нелінійних диференціально-операторних рівнянь у банахових просторах - Люстик, М.; Прикарпатський, А.К.; Притула, М.М.; Вовк, М.I. (Нелінійні коливання, 2009)
Развивается проекционно-алгебраический метод дискретных аппроксимаций типа Калоджеро для линейных дифференциальных уравнений в банаховых пространствах, проведен анализ
сходимости конечномерных аппроксимаций, базирующийся на функционально-алгебраическом
подходе к дискретным аппроксимациям и методах теории операторов в банаховых пространствах. Рассмотрены применения полученных результатов к функционально-интерполяционной
схеме проекционно-алгебраического метода дискретных аппроксимаций. На основании обобщенного утверждения типа Лере – Шаудера рассмотрена проекционно-алгебраическая схема
дискретных аппроксимаций и проанализированы ее разрешимость и сходимость для специального класса нелинейных операторных уравнений. The projection-algebraic method of the Calogero type for discrete approximations of linear differential
equations in Banach spaces is developed, the convergence analysis of the corresponding finite-dimensional
expressions, based on the functional-analytic approach to discrete approximations and methods of operator
theory in Banach spaces, is presented. Application of the obtained results to the functional-interpolation
scheme of the projection-algebraic method of discrete approximations is considered. Based on a generalized Leray – Schauder type theorem the projection-algebraic scheme of discrete approximations is proposed,
its solvability and convergence for a special class of nonlinear operator equations is analyzed.